What Postgraduates Appreciate in Online Tutor Feedback on Academic Writing - Northcott, Jill; Gillies, Pauline; David Caulton, David (Journal of Academic Writing, 2016)
Improving postgraduate student writing in English is an ongoing concern in the increasingly internationalised UK Higher Education context. Although the importance of feedback for developing academic writing skills is well-established (Hyland and Hyland 2006), there is still much debate about the components of effective feedback. In response to the call for research investigating teachers’ real-world practices in giving feedback in specific contexts (Lee 2014 and 2012), this article presents an initiative to develop students’ abilities to tackle written postgraduate writing (essays and dissertations) through collaborative on-line academic writing courses. The Grounded Theory-inspired study explores student perceptions of the effectiveness of online formative feedback on postgraduate academic writing in order to identify best practices which can contribute to developing skills in providing feedback. The study analyses tutor feedback on student texts and student responses to feedback. We applied categories which emerged from this data and concluded that the students we investigated had responded most positively when a combination of confidence-developing feedback practices were employed. These included both principled corrective language feedback and positive, personalised feedback on academic conventions and practices. This collaboration between academic writing and content specialists continues to provide further opportunities for embedding practices that encourage the development of academic writing skills on one year postgraduate programmes at the University of Edinburgh.